Invited review Novel vaccines against Theileria parva: prospects for sustainability - McKeever, Declan J.; Morrison, W. Ivan (Elsevier, 1998)
A first-gneration subunit vaccine for East Coast fever based on the Theileria parva p67 sporozoite surface antigen is entering preliminary field trials. Intensive efforts are also focused on the identification of a schizont-specific omponen for incorporation in a second-generation multi-component product. It is clear that many questions remain unanswered regarding the likely performance of these vaccines under field conditions. In particular their effect on the endemic status of the parasite in targeted areas will be crucial to their sustainability. Ideally, challenge should be maintained so that immunity is boosted in the absence of repeat vaccination. In the event that efficacy of the p67 vaccine in the field reflects that observed in extensive laboratory trials, it is possible that some reduction in the heterogeneity of the indigenous parasite population will occur, and this may be accompanied by selection for more highly infective strains. In contrast, available information suggests that schizont-specific components of a second-generation subunit vaccine are unlikely to affect the endemic status of parasite populations. However, endemic stability will inevitably decline as management systems become more intensive and necessitate frequent vaccination to maintain protective cover.